(untitled) (The Pakistan Development Review, 2007)
Agriculture has now been seen in its multiple roles like contributing to development as an economic activity, source of livelihood, provider of environmental services and a unique instrument to overall development. As an economic activity, it is a source of growth for national economy, food security, foreign exchange as well as provider of investment opportunities for agro-based industries and rural non-farm economy. As source of livelihood, it provides jobs to majority of the people, especially the small holders, landless and the poor. In terms of environmental services, being the major player in underground water depletion, agrochemical pollution, soil exhaustion and global climate change due to greenhouse gas emissions, agriculture can create good and bad environmental outcomes. Its environmental contributions in managing watersheds and preserving biodiversity are generally unrecognised and unremunerated. Agriculture has well established record as an instrument for poverty reduction1 as well as a leading sector for overall growth in the agriculture-based countries of the world [World Bank (2007)]. In future, agriculture has to commit more promises (e.g. bio-fuel) to the nation without compromising over primary responsibility of food security along with poverty alleviation, conservation of natural resource base, environment protection etc. Unfortunately, the agriculture has been vastly underused for development.